1988
DOI: 10.1159/000469136
|View full text |Cite
|
Sign up to set email alerts
|

Source of Increased Serum Beta-Hexosaminidase in Rat Liver Cirrhosis

Abstract: Lysosomal enzymes were studied by histo- and biochemical methods in cirrhotic rat livers in order to explain the serum increase of lysosomal enzymes in cirrhosis. Biochemically, the most evident increase was found in isolated hepatocytes. Histochemically, the lysosomal enzymes were increased mainly in rows of macrophages and necrotic or atrophic hepatocytes adjacent to strands of connective tissue at the periphery of the cirrhotic nodules. The results were compared to similar studies in cholestatic rats. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…Similarly, in this study äs in our earlier reports (3,6), the autophagocytotic process in degenerating cells is combined with an inerease of ß-hexosaminidase-positive granules, probably lysosomes. Confer & Stenger (20) and Kanashima et al (21) also found that degenerating hepatocytes initially respond by increasing the nümber of their lysosomes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similarly, in this study äs in our earlier reports (3,6), the autophagocytotic process in degenerating cells is combined with an inerease of ß-hexosaminidase-positive granules, probably lysosomes. Confer & Stenger (20) and Kanashima et al (21) also found that degenerating hepatocytes initially respond by increasing the nümber of their lysosomes.…”
Section: Discussionsupporting
confidence: 90%
“…From earlier o f high molecular mass. Via specific (mannose-6-phosstudies in humans and rats we küow that the lysosomal phate) receptors, most of these precursors are transenzyme, ß-hexosaminidase, 1 ) is increased in serum äs ported to the lysosomes, where they are subsequently well äs in liver and spieen tissue in cholestasis and cir-dephosphorylated and proteolytically processed to genrhosis (2)(3)(4)(5). In long Standing experimental cholestasis, erate lysosomally localized mature forms (7,8).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In fact, Melén et al [5] found that, in intragastric CCl4-induced rat liver cirrhosis [16], the increase in serum Hex levels was greater in animals with more deteriorated liver function tests. Hultberg et al [8] re cently showed that most of the increased serum Hex activity in rat liver cirrhosis is derived from parenchymal liver cells, mainly from necrotic or atrophic hepatocytes. In man, Isaksson et al [4] found serum Hex activity much more increased in patients with alcoholic liver cirrhosis than in chronic alcoholics, who probably only had liver stea tosis.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of Hex activity in the sera and liver tissue was performed according to Hultberg et al [8] as follows. 50 pi 7.5 mmol/1 nitrophenyl-2-acetamidodeoxy-B-D-glucopyranoside (from Sigma Chemical Co., St. Louis, Mo., USA), and 50 pi 1 mol/1 citrate buffer (pH 4.5) and 100 pi plasma (or liver homogenate) were incubated at 37 °C for 30 min.…”
Section: Biochemical Determinationsmentioning
confidence: 99%